MSME Strategy Planning Using the SWOT and IE Matrix Analysis Approach - Wahyudin Wahyudin; Dene Herwanto; Billy Nugraha (International Journal of Economics Development Research (IJEDR), 2023)
The goal of MSME Farida Snack and APHE is to develop skin crackers that are more valuable in the perspective of customers. Taking into account that the COVID-19 pandemic is still causing economic instability today. Because of this, MSME participants must conduct strategic analysis in order to continue operating their business. With the intention of strengthening the MSME strategy through this research. Utilizing study locations in Karawang Regency, a SWOT analysis was undertaken. The research findings based on Swot analysis and actionable recommendations. Thus, using the S-O (Strength-Opportunities), W-O (Weaknesses-Opportunities), S-T (Strength-Threat), and W-T (Weaknesses-Threat) data, a SWOT matrix was created. In order to generate alternative strategies, the SWOT matrix attempts to match opportunities and threats as an external aspect encountered by firms with weaknesses as internal factors. The SWOT matrix, which is a matrix of nine cells each holding four potential cell methods, is used in the study. Next, the study's development took the outcomes of the IFE and EFE analyses into consideration. Next, using the findings of the IE analysis, the position and state of MSMEs.